Codoping of Nickel and Nitrogen in ZrO2-TiO2 Composite as Photocatalyst for Methylene Blue Degradation under Visible Light Irradiation - Syoufian, Akhmad; Kurniawan, Rian (Indonesian Journal of Chemistry, 2024)
Nickel (Ni) and nitrogen (N) as codopants had been introduced into ZrO2-TiO2 composite photocatalyst. The objectives of this study are to investigate the codoping effect of Ni and N, as well as the calcination temperature towards the ability to photodegrade methylene blue (MB) under the irradiation of visible light. Different amounts of Ni dopant (wNi/wTi = 2–10%) along with a fixed amount of N dopant (wN/wTi = 10%) were applied to the ZrO2-TiO2 composite through the sol-gel method. Crystallization of the composite was done by calcination at 500, 700, and 900 °C. Characterization of the composite was done using Fourier-transform infrared spectrophotometer (FTIR), X-ray diffractometer (XRD), specular reflectance UV-visible spectrophotometer (SR-UV) and scanning electron microscopy equipped with energy dispersive X-ray spectrometer (SEM-EDX). The photocatalytic activity of the composite was evaluated by photodegradation of 4 mg L−1 MB solution under visible light irradiation at various reaction times. The lowest band gap was achieved until 2.79 eV by the composite with 6% Ni and 10% N calcined at 900 °C. The highest MB degradation percentage up to 61% was obtained by the composite with 6% Ni and 10% N calcined at 500 °C (kobs = 7.8 × 10−3 min−1).